Cooling in the X-ray halo of the rotating, massive early-type galaxy NGC 7049. Issue 2 (17th January 2019) - Juráňová, A; Werner, N; Gaspari, M; Lakhchaura, K; Nulsen, P E J; Sun, M; Canning, R E A; Allen, S W; Simionescu, A; Oonk, J B R; Connor, T; Donahue, M
ABSTRACT: The relative importance of the physical processes shaping the thermodynamics of the hot gas permeating rotating, massive early-type galaxies is expected to be different from that in non-rotating systems. Here, we report the results of the analysis of XMM–Newton data for the massive, lenticular galaxy NGC 7049. The galaxy harbours a dusty disc of cool gas and is surrounded by an extended hot X-ray emitting gaseous atmosphere with unusually high central entropy. The hot gas in the plane of rotation of the cool dusty disc has a multitemperature structure, consistent with ongoing cooling. We conclude that the rotational support of the hot gas is likely capable of altering the multiphase condensation regardless of the t cool / t ff ratio, which is here relatively high, ∼40. However, the measured ratio of cooling time and eddy turnover time around unity ( C -ratio ≈ 1) implies significant condensation, and at the same time, the constrained ratio of rotational velocity and the velocity dispersion (turbulent Taylor number) Tat > 1 indicates that the condensing gas should follow non-radial orbits forming a disc instead of filaments. This is in agreement with hydrodynamical simulations of massive rotating galaxies predicting a similarly extended multiphase disc.